PENGARUH KOLABORASI DAN EVALUASI DALAM SUPPLY CHAIN PADA INVESTASI LINGKUNGAN DI LEVEL PRODUSEN (STUDI KASUS: PADA PERUSAHAAN FOOD INDUSTRY DI KOTA MEDAN) - Julita, Mawardi Nur (Jurnal Riset Akuntansi dan Bisnis, 2010)
This study aims to empirically testing the influence of collaborative activitybetween the factory with customers and suppliers on environmental investments atthe level of producers in the allocation of Pollution Prevention and empirically testthe influence of the evaluation activities of the factory with customers and supplierson environmental investments in the allocation of producer dilevel Pollution Controland test empirically the influence of collaboration and evaluation activities of thefactory with consumers and suppliers are allocated in the Pollution Prevention andPollution Control jointly on environmental nvestasi producers dilevel.This study uses primary data to test hypotheses on the data collectionmethods of this research is to use survey methods, the research instrument in theform of a questionnaire distributed by way of coming each company according to thelist of food industry companies in the city of Medan.Research results showed thatoverall the process of collaboration with customers and suppliers with consumersyng producers showed a positive impact on the environment nestasiform.Nevertheless, very real collaborative process occurs only on the supplier by themanufacturer.Whereas collaboration between consumers and producers are still alittle place or in other words, the involvement of consumers in providing input ordirectly involved in efforts to improve the environment for investments is still verysmall producers. The process of evaluation both from consumers and suppliers to theproducers still felt lacking. Even in the evaluation process that involved consumersvirtually nothing, where both the industry biscuits, snacks and bakery can not find asignificant influence. In the evaluation process, the real impact on the industry onlybiscuits and snack food industry, only affect the level of 10%. The process ofcollaboration and evaluation by consumers and suppliers to the producers as awhole can improve the investment environment in the food industry (FoodIndustry). Although the bakery industry both of these activities have not shownsignificant results on improving the investment environment.